Processing of pyrite derived from coal mining waste by density separation technique using lithium heteropolytungstate (LST) - Ghedin,Sara C. D. (2022)
ABSTRACT Pyrite (FeS2) is one of the main tailings derived from coal mining. When processed, pyrite has several applications with high value-added, in contrast, if improperly discarded, it causes major environmental impacts, like the acid mine drainage. For those reasons, the seeking for beneficiation techniques of Pyrite has been the target of numerous studies. One of the most employed techniques is the separation by density using heavy liquids, like bromoform, as a separation medium. In the present work, we propose the use of lithium heteropolytungstate (LST), a non-halogenated and non-toxic solution, as an alternative in the separation by density method. For the experiments, raw pyrite samples were collected from the tailings of coal extraction from a mining company in Santa Catarina, Brazil. After the separation process, the samples before and after the beneficiation were characterized by XRD, FTIR, and XRF techniques. The results revealed that the separation technique used in this work led to a significant increase in the concentration of pyrite, going from less than 10% in the raw sample and reaching almost 80% after processing. This impressive result reveals that LST represents a promising alternative for separating pyrite by density techniques, showing much greater effectiveness than other heavy liquids used in the literature, in addition to being environmentally friendly.